Lietuvos TSR biochemikų darbų citavimas pasaulio literatūroje - Voverienė, Ona; Paliukienė, Rasa (Knygotyra, 1988)
In the article, a short review of Lithuanian authors' research is provided, using the "Science Citation Index." The analysis of citation data is conducted to determine in which countries Lithuanian biochemists' works are disseminated, the main sources in which these works are most frequently cited, the "half-life" of literature in biochemistry, the most cited authors, and their interactions with scientists both domestically and internationally.